The Philippine islands, 1493-1803 explorations by early navigators, descriptions of the islands and their peoples, their history and records of the Catholic missions, as related in contemporaneous books and manuscripts, showing the political, economic, commercial and religious conditions of those islands from their earliest relations with European nations to the beginning of the nineteenth century - Blair, Emma Helen d.1911; Robertson, James Alexander 1873-1939; Bourne, Edward Gaylord 1860-1908 (A.H. Clark, 1903)
The next attempt to reach the Spice Islands is made by Garcia Jofre de Loaisa. A synopsis of contemporary documents is here presented: discussion as to the location of the India House of Trade; concessions offered by the Spanish government to persons who aid in equipping expeditions for the Moluccas; instructions to Loaisa and his subordinates for the conduct of their enterprise; accounts of their voyage, etc.